A Novel Oscillatory Pressure‐Assisted Hot Pressing for Preparation of High‐Performance Ceramics. Issue 4 (13th March 2014) - Xie, Zhipeng; Li, Shuang; An, Linan; Franks, G.
<x xml:space="preserve">Abstract</x> We report a novel oscillatory pressure‐assisted hot‐pressing process for preparing high‐quality ceramics. Compared with the samples prepared by conventional pressureless sintering (PS) and hot‐pressing (HP), the zirconia ceramic prepared by oscillatory pressure‐assisted hot‐pressing (OPAHP) exhibited a higher density, smaller grain size, and more homogeneous structure. More remarkably, the strength of the OPAHP sample reached 1556 MPa, which is much higher than the samples prepared by other two techniques. The results suggest that OPAHP is a more effective technique for preparing high‐quality zirconia, which is likely applicable to other material systems.